2023
DOI: 10.1002/jmv.28761
|View full text |Cite
|
Sign up to set email alerts
|

Integration and viral oncogene expression of human papillomavirus type 16 in oropharyngeal squamous cell carcinoma and gastric cancer

Abstract: Persistent high-risk human papillomavirus (HR-HPV) infections cause cervical cancer and a fraction of head and neck cancer. To investigate whether HR-HPV infection might be also involved in the development of gastric cancer (GC), we developed a platform utilizing a rolling circle amplification (RCA)-based nested L1 polymerase chain reaction with Sanger sequencing to genotype the HPV DNA in cancer tissues of 361 GC and 89 oropharyngeal squamous cell carcinomas (OPSCC). HPV transcriptional activity was determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
(140 reference statements)
0
2
0
Order By: Relevance
“…A meta-analysis has revealed a positive relationship between HPV16 infection and the risk of gastric cancer development. 14 Studies have shown that the occurrence of gastric cancer in Zambia is related to the antibody to the early antigen of EBV, but not to EBV Nuclear Antigen-1. The impact of reactivation of EBV on gastric carcinogenesis in Zambia, where an association between EBV early antigens and HIV-positivity has been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis has revealed a positive relationship between HPV16 infection and the risk of gastric cancer development. 14 Studies have shown that the occurrence of gastric cancer in Zambia is related to the antibody to the early antigen of EBV, but not to EBV Nuclear Antigen-1. The impact of reactivation of EBV on gastric carcinogenesis in Zambia, where an association between EBV early antigens and HIV-positivity has been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, there were significant variations in HPV status between Chinese and non-Chinese studies. Notably, HPV positivity was 1.43-times higher in Chinese GC patients than in non-Chinese patients, indicating a potential association between HPV infection and GC development in the Chinese population [202]. However, another study did not detect HPV DNA in the gastric mucosa tissue of GC patients in China [203].…”
Section: Clinical Significance Of Hpv In Gcmentioning
confidence: 96%